Caracterização e avaliação da toxicidade da berberina encapsulada com Poloxamer 407 em Drosophila melanogaster - Leao, Dayane Alves (2021)
Berberine is an isoquinoline alkaloid, of bitter taste and yellow color, presenting multiple pharmacological and biological activities, has characteristics already known as antioxidants, anti-inflammatory and neuroprotective. Its low bioavailability, water insolubility and instability limit its application, hindering its action and absorption. Therefore, nanotechnology has attracted a lot of attention because it can alter berberine absorption and modify its effects,both in vivo and ex vivo. Several techniques can be used to improve the dissolution and bioavailability of bioactive with low solubility in water, among them there are solid dispersions. However, up to now, little is known in relation to the toxicity of berberinecontaining nanoparticles in animal models. For this, Drosophila Melanogaster (DM) known as fruit fly has been used as an excellent model for the investigation of nanoparticle toxicity. Thus, the objective of this work is the production of berberine nanoparticles and to evaluate the toxicity in Drosophila Melanogaster as an alternative biological model. Berberine nanoencapsulation with the encapsulant Poloxamer 407 (P407) was obtained through the solid dispersion technique by solvent evaporation. Nanoparticles (NPs), as well as free berberine (BBR), Poloxamer 407 and physical mixture (BBR + P407) were characterized by differential scanning calorimetry (DSC), Fourier transform infrared spectrophotometry (FTIR), electronic spectroscopy in the UV-VISregion. The pH of NPs and BBR solutions was also performed within 60 days, exposed to light or stored in amber vials, in order to verify the chemical stability of the compounds. The characterization of the nanoparticles evidenced a change in the physical state of berberine free from the crystalline state to amorphus, demonstrating efficiency in encapsulation. In the analysis of DSC for free berberine we observed several thermal events, with a broad exothermic peak where they are added to the vitreous transition region (Tg), cold crystallization region and melting process (Tm), with a degree of crystalline (Xc %) 74.60%. The P407 obtained an exothermic peak early on (61.7ºC) reaching a degree of crystallinity of 124.82% and a Tg 55ºC, and both nanoparticles and physical mixture presented thermal events at the beginning. The results obtained show that the FTIR spectra in some regions showed different functional groups, with free berberine bands around 3095 cm-1 to 3600 cm-1, referring to the stretch =CH sp2, still vibrations at 2900 cm-1 referring to the CH3 methyl group in the nanoparticles and bands 2289 cm-1 and 2883 cm-1. From the monitoring of the pH of BBr NPs and free BBR solutions, it can be noted that there were no changes in 60 days of measurement. For BBR NPs stored in amber vials the pH was 5.93, while BBR NPs exposed to light the pH was 5.74, for the free BBR in amber bottle the pH=6.04 and exposed to pH=6.07 light, respectively. Thus, both BBR NPs and BBR free showed chemical stability, which was also evidenced by UVVIS in the initial and final solutions. After optimization of the synthesis conditions, unfiltered berberine NPs with a mean diameter of approximately 218.5 nm and filtered berberine NPs of 307.4 nm and Zeta potential of -3.15 and -5.34 mV were obtained. In vivo results using Drosophila Melanogaster showed that nanoparticles containing berberine promoted a significant mortality rate, whereas the treatment containing Free BBr and Free BBr_EtOH at all concentrations did not show significant changes in the survival rate when compared to the control. Change in locomotor performance of flies supplemented with Free BBr, Free BBr_EtOH, NPs BBr exhibited a dose-dependent significant motor deficit. The open field test shows that the group exposed to Free BBr and Free BBr_EtOH at a concentration of 30 µM showed lower exploratory activity when compared to the control group with NPs BBr, the concentration that showed lower exploratory activity was 10 µM. Cell viability assays showed that the survival rate with samples of Free BBr, Free BBr_EtOH and most BBr NPs were above 90%, which indicates a low cytotoxicity for all samples. In the diet supplemented using bright blue food coloring, Drosophilas Melanogaster decreased consumption in the treatment with Free BBr and in the treatments with Free BBr_EtOH and NPs BBr had a consumption greater than 90%. In ex vivo tests, there was no inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) activity. The results indicate that it was possible to encapsulate berberine in the polymeric matrix, as well as showing low toxicity, suggesting the use of alternative biological models.